Ultra-Fast Processing of Gigapixel Tissue MicroArray Images Using High Performance Computing - Yinhai Wang; David McCleary; Ching-Wei Wang; Paul Kelly; Jackie James; Dean A. Fennell; Peter Hamilton (Analytical Cellular Pathology)
Background: Tissue MicroArrays (TMAs) are a valuable platform for tissue based translational research and the discovery of tissue biomarkers. The digitised TMA slides or TMA Virtual Slides, are ultra-large digital images, and can contain several hundred samples. The processing of such slides is time-consuming, bottlenecking a potentially high throughput platform.